The use of pharmacological protocols during the Covid-19 crisis - a déjà vu of the 2009 A/H1N1 pandemic experience - Jimenez Alonso, Wladimir; Schuck-Paim, Cynthia; Diez Vicera, Veronique (InterAmerican Journal of Medicine and Health, 2020)
Only one decade ago, the World Health Organization declared the outbreak of a novel influenza A (H1N1) virus a worldwide pandemic. Then, just as in today’s Covid-19 crisis, treatment options were the center of debate, one of which is of special importance to the current pandemic: the existence of pharmacological treatments that, although available and potentially effective, are approached with reluctance due to concerns around side effects, the development of resistance and lack of conclusive evidence of effectiveness from randomized-controlled trials. History has proven that reluctance to use antivirals during the 2009 A/H1N1 pandemic was unwise, as those countries that restricted their use to at-risk groups and to patients with advanced disease experienced higher mortality. Those same antiviral are now routinely used for seasonal influenza. We revisit this forgotten lesson as a means of weighing in on the debate over the use of new treatments with promising outcomes as observed in clinical practice, but lacking strong evidence from controlled trials, which require a time frame incompatible with that available in unfolding public health emergencies triggered by novel pathogens.